Esophageal adenocarcinoma and Barrett esophagus in a neurologically impaired teenager. Issue 11 (23rd November 2016) - Hwang, Jae‐Yeon; Lee, Yeoun Joo; Chun, Peter; Shin, Dong Hoon; Park, Jae Hong
Abstract: Esophageal adenocarcinoma (EAC) accompanied by Barrett esophagus (BE) is rare in patients younger than 20 years old. EAC in the upper esophagus is also rare. We report a rare case of EAC with BE that developed in the upper esophagus after chronic, untreated gastroesophageal reflux disease in a neurologically impaired teenager. A 19‐year‐old neurologically impaired man underwent endoscopy for evaluation of dysphagia and vomiting, and was diagnosed with EAC with BE. He underwent transthoracic esophagectomy, extensive lymph node dissection, and cervical esophagogastric anastomosis, but the prognosis was poor. Pathology indicated poorly differentiated adenocarcinoma with BE.